Distributed Agent-Based Online Auction System - Bădică, Costin; Ilie, Sorin; Muscar, Alex; Bădică, Amelia; Sandu, Liviu; Sbora, Raluca; Ganzha, Maria; Paprzycki, Marcin (Computing and Informatics, 2015)
This paper concerns the design and development of a distributed agent-based online system for English auctions. The proposed system is composed of two parts: an Agent-based Auction Server and a Web-based Graphical User Interface. The first part of our work brought about the advantages introduced by the multi-agent systems technology to the high-level of abstraction, modularity and performance of the server architecture and its implementation. On the server side, bids submitted by auction participants are handled by a hierarchical organization of agents that can be efficiently distributed on a computer network. This approach avoids the bottlenecks of bid processing that might occur during periods of heavy bidding, like for example snipping. We present experimental results that show a significant improvement of the server throughput compared with the architecture where a single auction manager agent is used for coordinating the participants for each active auction that is registered with the server. The second part of our work involved analysis of external functionalities, implementation and usability of a prototype online auction system that incorporates the Agent-based Auction Server. Our solution is outlined in terms of information flow management and its relation to the functionalities of the system. The main outcome of this part of the work is a clean specification of the information exchanges between the agent and non-agent software components of the system. Special attention is also given to the interoperability, understood here as successful integration of the different data communication protocols and software technologies that we employed for the implementation of the system.